Perinatal transmission in infants of mothers with chronic hepatitis B in California - Burgis, Jennifer C (World J Gastroenterol, 2017)
AIM: To evaluate maternal hepatitis B virus (HBV) DNA as risk for perinatal HBV infection among infants of HBV-infected women in California. METHODS: Retrospective analysis among infants born to hepatitis B surface antigen (HBsAg)-positive mothers who received post vaccination serologic testing (PVST) between 2005 and 2011 in California. Demographic information was collected from the California Department of Public Health Perinatal Hepatitis B Program databaseand matched to birth certificate records. HBV DNA level and hepatitis B e antigen (HBeAg) status were obtained from three large commercial laboratories in California and provider records if available and matched to mother infant pairs. Univariate analysis compared infected and uninfected infants. Multivariate analysis was restricted to infected infants and controls with complete maternal HBV DNA results using a predefined high HBV DNA level of > 2 × 10(7) IU/mL, a 5:1 ratio of cases to controls and a two-sided confidence level of 95%. RESULTS: A total of 17687 infants were born to HBsAg positive mothers in California between Jan 1 2005 and Dec 31, 2011. Among 11473 infants with PVST, only 125 (1.1%) were found to be HBV infected. Among these infected infants, lapses in Advisory Committee on Immunization Practices recommended post exposure prophylaxis (PEP) occurred in only 9 infants. However, PEP errors were not significantly different between infected and uninfected infants. Among the 347 uninfected and infected infants who had maternal HBeAg and HBV DNA level, case-control analysis found HBeAg positivity (70.4% vs 28.9%, OR = 46.76, 95%CI: 6.05-361.32, P < 0.001) and a maternal HBV DNA level ≥ 2 × 10(7) IU/mL (92.6% vs 18.5%, OR = 54.5, 95%CI: 12.22-247.55, P < 0.001) were associated with perinatal HBV infection. In multivariate logistic regression, maternal HBV DNA level ≥ 2 × 10(7) IU/mL was the only significant independent predictor of perinatal HBV infection. CONCLUSION: In California, transmission is low and most infected infants receive appropriate PEP and vaccination. Maternal HBV DNA ≥ 2 × 10(7) IU/mL is associated with high risk of perinatal infection.